High-Density Physical Random Number Generator Using Spin Signals in Multidomain Ferromagnetic Layer - Sungwoo Chun; Seung-Beck Lee; Masahiko Hara; Wanjun Park; Song-Ju Kim (Advances in Condensed Matter Physics)
A high-density random number generator (RNG) based on spin signals in a multidomain ferromagnetic layer in a magnetic tunnel junction (MTJ) is proposed and fabricated. Unlike conventional spin-based RNGs, the proposed method does not require one to control an applied current, leading to a time delay in the system. RNG demonstrations are performed at room temperature. The randomness of the bit sequences generated by the proposed RNG is verified using the FIPS 140-2 statistical test suite provided by the NIST. The test results validate the effectiveness of the proposed RNGs. Our results suggest that we can obtain high-density, ultrafast RNGs if we can achieve high integration on the chip.